2022
DOI: 10.1002/tox.23705
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene microplastic particles induce autophagic cell death in BEAS‐2B human bronchial epithelial cells

Abstract: The detection of high levels of microplastics in indoor and outdoor air has increased concerns regarding its toxic effects on the respiratory system. They are not easily degradable and can be deposited deep in the lungs. Although several studies have reported inhalation toxicities of microplastics, they are still controversial due to a lack of evidence. Herein, we evaluated the inhalation toxicities of three differently charged polystyrene microplastics (PS-MPs), the most abundant microplastics in the air. Cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 57 publications
0
8
1
Order By: Relevance
“…Provided that the increase of SSC intensity represented the uptake of particles in cells, the concentration-dependent increase of SSC by secondary MPs suggested that phototransformation enhanced the cellular uptake of MPs, in contrast to the nearly unchanged SSC intensity for original EMPs (Figure a). Due to the close contact of MPs on the cell membrane, the positively charged MPs showed higher cytotoxicity than the negatively charged MPs, which was opposite to the higher cytotoxicity caused by the carbonyl MPs in this study. However, fragmentation of MPs was induced by photocatalysis, possibly leading to different contacting behavior of MPs on cell surface.…”
Section: Resultscontrasting
confidence: 75%
“…Provided that the increase of SSC intensity represented the uptake of particles in cells, the concentration-dependent increase of SSC by secondary MPs suggested that phototransformation enhanced the cellular uptake of MPs, in contrast to the nearly unchanged SSC intensity for original EMPs (Figure a). Due to the close contact of MPs on the cell membrane, the positively charged MPs showed higher cytotoxicity than the negatively charged MPs, which was opposite to the higher cytotoxicity caused by the carbonyl MPs in this study. However, fragmentation of MPs was induced by photocatalysis, possibly leading to different contacting behavior of MPs on cell surface.…”
Section: Resultscontrasting
confidence: 75%
“…However, plastic-related compounds may reduce this capacity by disrupting mitosis and DNA replication, blocking hepatocytes in G0/G1 phase. Moreover, the suppression of mitosis may cause cell death [ 82 , 83 ]. Regarding compounds 4 and 5 , the activation of pathways involved in autophagy was identified (such as ‘autophagy’ and ‘process utilizing autophagic mechanism’).…”
Section: Discussionmentioning
confidence: 99%
“…The results also depended on particle charge; only positively-charged particles (NH 2 -PS-MPs) triggered mechanisms that led to the initiation of different types of cell death. The results demonstrated that NH 2 -PS-MPs induced autophagic cell death in bronchial epithelial cells, leading to inflammatory responses in the lungs [58].…”
Section: Hemolysis Accidental Death In Anucleated Cellsmentioning
confidence: 90%